Humans as Cultured, Ethical, and Aesthetic Beings: A Conceptual Study - Prayogi, Arditya; Prasetya, Dimas (STAI Darul Kamal NW Kembang Kerang, 2023)
Conceptual study of humans as human beings with culture, ethics, and aesthetics is still developing considering that humans are complex entities that still require various understandings. Thus, this article attempts to elaborate on conceptual studies as part of enriching discourse and understanding of humans. This article is a literature review written using a qualitative descriptive approach. From the results of the study, it was found that the pattern of relations between humans and culture cannot be separated from one another. Humans are creators of culture. The creation of culture is the result of human interaction with all aspects of life, both abstractly and concretely. Culture was born because of humans, so as long as humans remain on earth, culture will also remain sustainable. In its development, culture then continues to experience dynamics in dialectics because of the role of humans who carry out or maintain this culture.